2018
DOI: 10.1002/mgg3.395
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing panel based on single molecule molecular inversion probes for detecting genetic variants in children with hypopituitarism

Abstract: BackgroundCongenital Hypopituitarism is caused by genetic and environmental factors. Over 30 genes have been implicated in isolated and/or combined pituitary hormone deficiency. The etiology remains unknown for up to 80% of the patients, but most cases have been analyzed by limited candidate gene screening. Mutations in the PROP1 gene are the most common known cause, and the frequency of mutations in this gene varies greatly by ethnicity. We designed a custom array to assess the frequency of mutations in known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 112 publications
(137 reference statements)
3
10
0
1
Order By: Relevance
“…The mutant RARB protein showed reduced expression and translocation to the nucleus compared with the wild-type protein while the RXRA showed no difference in localization. DMSO Perez Millan et al, 2018;Redin et al, 2014). A recent report on diagnosing genetic developmental eye disorders indicated a low diagnostic yield of 8% for microphthalmia, anophthalmia, and coloboma disease, similar to the yield reported here (Patel, Hayward et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The mutant RARB protein showed reduced expression and translocation to the nucleus compared with the wild-type protein while the RXRA showed no difference in localization. DMSO Perez Millan et al, 2018;Redin et al, 2014). A recent report on diagnosing genetic developmental eye disorders indicated a low diagnostic yield of 8% for microphthalmia, anophthalmia, and coloboma disease, similar to the yield reported here (Patel, Hayward et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…We identified novel variants in genes such as TFAP2A and CHD7 , and previously reported variants in RARB and BMP7 , indicating that mutations in known coloboma‐associated genes account for only 4.5% of the coloboma cohort analyzed. Congenital disorders such as coloboma and other conditions were shown to exhibit high genetic heterogeneity and targeted sequencing of disease‐associated genes may yield the limited outcome of potential variants (DaRe, Vasta, Penn, Tran, & Hahn, ; Perez Millan et al, ; Redin et al, ). A recent report on diagnosing genetic developmental eye disorders indicated a low diagnostic yield of 8% for microphthalmia, anophthalmia, and coloboma disease, similar to the yield reported here (Patel, Hayward et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our data (Tables 1 and 3), several studies have demonstrated that MIPs-NGS is an efficient and inexpensive method for detection of genetic variations in multiple diseases [25,32,37,38]. For example, Zhang et al and Pérez Millán et al presented in their studies the use of MIPs based NGS panels to detect pathogenic mutations in early-onset colorectal cancer patients and in patients with hypopituitarism, respectively [37,38]. Another potential application of MIPs-NGS is to target noncoding and low covered regions in WES.…”
Section: Plos Onesupporting
confidence: 91%
“…In the era of massive parallel sequencing methods, the number of genes involved in pituitary functioning was broaden dramatically, evidencing a huge complexity of developmental processes [6]. Even though, for numerous cases with clinical features indicative for CPHD, the causative genetic background cannot be identified [7]. Recent research provided new evidence on the cumulative effect of mild variants and oligogenicity, indicating a great abundance of possible contributors affecting pituitary organogenesis, but also evidencing unusual non-mendelian transmission [8,9].…”
Section: Introductionmentioning
confidence: 99%